2017
DOI: 10.24246/ijpna.v2i1.47-53
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design of Collimator at Boron Neutron Capture Therapy Facility with 30 MeV Cyclotron and Target 9Be as Neutron Generator Using Monte Carlo N-Particle Extended Simulator

Abstract: The optimization of collimator has been studied which resulted epithermal neutron beam for Boron Neutron Capture Therapy (BNCT) using Monte Carlo N Particle Extended (MCNPX). Cyclotron 30 MeV and 9 Be target is used as a neutron generator. The design criteria were based on recommendation from IAEA. Mcnpx calculations indicated by using 25 cm and 40 cm thickness of PbF2 as reflector and back reflector, 15 cm thickness of TiF3 as first moderator, 35 cm thickness of AlF3 as second moderator, 25 cm thickness of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The previous BSA design of Isyan et al (2017) is shown in Figure 1. In this research we focus on optimizing the BSA design especially in two parameters; those are the ratio of gamma dose rate and epithermal neutron flux, and the ratio of particle current and total flux.…”
Section: Geometry Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…The previous BSA design of Isyan et al (2017) is shown in Figure 1. In this research we focus on optimizing the BSA design especially in two parameters; those are the ratio of gamma dose rate and epithermal neutron flux, and the ratio of particle current and total flux.…”
Section: Geometry Modellingmentioning
confidence: 99%
“…PbF2 is chosen as a reflector based on Isyan's design (Isyan et al 2017). It performs well in reflecting the neutron beam.…”
Section: Reflectormentioning
confidence: 99%
See 3 more Smart Citations